2013
DOI: 10.1152/jn.00785.2012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in corticospinal excitability during reach adaptation in force fields

Abstract: Both abrupt and gradually imposed perturbations produce adaptive changes in motor output, but the neural basis of adaptation may be distinct. Here, we measured the state of the primary motor cortex (M1) and the corticospinal network during adaptation by measuring motor-evoked potentials (MEPs) before reach onset using transcranial magnetic stimulation of M1. Subjects reached in a force field in a schedule in which the field was introduced either abruptly or gradually over many trials. In both groups, by end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 74 publications
(84 reference statements)
3
19
0
Order By: Relevance
“…If the M1 stores motor memory, changes in M1 excitability induced by motor skill learning will be associated with retention of learned motor skills. Previous study demonstrated that LTP-like plasticity is essential for performance retention [48,49]. In the present study, a reduction in the performance score during the first two blocks performed on Day 2 only occurred in the SSL group.…”
Section: Relationship Between Changes In M1 Excitability and Motor Sksupporting
confidence: 54%
“…If the M1 stores motor memory, changes in M1 excitability induced by motor skill learning will be associated with retention of learned motor skills. Previous study demonstrated that LTP-like plasticity is essential for performance retention [48,49]. In the present study, a reduction in the performance score during the first two blocks performed on Day 2 only occurred in the SSL group.…”
Section: Relationship Between Changes In M1 Excitability and Motor Sksupporting
confidence: 54%
“…In support of this idea, (Alaerts et al, 2011) have shown that, in a blocked design, visual information about object weight from previously observed lifts drives cortico-spinal excitability before visual information about object weight in an upcoming observed lift is available. These low-level modulations may even serve a behavioural function, given the growing experimental evidence for a link between cortico-spinal excitability and motor output (Bagce et al, 2013;Klein-Flügge et al, 2013;Orban de Xivry et al, 2013). In the context of object lifting, Loh et al, (2010) have provided strong evidence that cortico-spinal excitability is related to fingertip force scaling by demonstrating that, in the same individuals, the ratio between MEPs before lifting for heavy and light objects correlates with the ratio for the force rates used to lift the same heavy and light objects.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of this motor memory appears independent of human medial temporal lobe structures (Shadmehr et al, 1998), but dependent on the integrity of the cerebellum (Smith and Shadmehr, 2005; Criscimagna-Hemminger et al, 2010; Donchin et al, 2012), and the motor cortex (Li et al, 2001; Richardson et al, 2006; Arce et al, 2010b; Orban de Xivry et al, 2011b; Orban de Xivry et al, 2011a; Orban de Xivry et al, 2013). In particular, a study in humans demonstrated that reversible disruption of the thalamic projections of the cerebellum to the cortex produced within-subject impairments in the ability to learn the force field task (Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%